[PP.20.23] INCREASED OXIDATIVE STRESS AND METALLOPROTEINASE ACTIVITY DURING EXPANSIVE VASCULAR REMODELING IN A MURINE MODEL OF VASCULAR CALCIFICATION AND DIABETES MELLITUS. (September 2017) - Carmo, L.; Almeida, Y.; Farias-Silva, E.; Alves, L.; Burdmann, E.; Liberman, M.
Abstract : Objective: vascular remodeling and calcification (highly prevalent in diabetes mellitus) have a pivotal role in cardiovascular disease. The aims of this study were to quantify and to assess mechanisms of vascular remodeling and calcification in obese insulin-resistant leptin deficient ob/ob mice (OB) after vitamin D3 stimulation (VD) or saline (C), compared with wild type (C57BL/6) mice. Design and method: the occurrence of ROS generation in the progression of vascular remodeling associated with calcification was tested by using 5, 5-Dimethyl-1-pyrroline N-oxide (DMPO) in vivo and quantified by anti-DMPO antibody. Leptin-deficient (OB, n = 12) and C57BL/6 mice (C57, n = 12) were injected with saline (C) or vitamin D3 8x104IU (VD) i.p. daily for 14 days. Results: are mean ± SE (statistical significance is p < 0.05 by ANOVA). Aorta from OBVD (+++) increased oxidative stress compared to wtVD and OBC (+), coincidently with augmented in situ metalloproteinase activity. Furthermore, aorta from OBVD increased both external and internal elastic lamina circumferential length (3478 ± 270 μm, p = 0.0001 and 3186 ± 263 μm, p = 0.0002) vs. OBC (2841 ± 75 μm and 2657 ± 71 μm), vs. C57VD (2611 ± 40 μm and 2333 ± 42 μm) and vs. C57C (2569 ± 165 μm and 2351 ± 168 μm), depicting outward vascular remodeling. Aortic wall thickness decreased significantly (24.3 ± 0.4 μm, p = 0.0001) in OBVD vs. OBC (29.7 ± 1.3 μm), vs. C57VD (34.4 ± 0.6 μm) and vs. C57C (39.0 ± 1.3 μm), indicating hypotrophic vascular remodeling (p < .05 for all, n = 6). OBVD exhibited more fibrosis (20130 ± 802 μm 2, p = 0.1538) vs. OBC (4565 ± 400 μm 2 ), elastolysis and total calcification burden (32310 ± 6790 vs. 4007 ± 854 μm 2, p = 0.0003). Vascular calcification area correlated with increased total vessel area (r2 = 0.8, p = 0.003). Conclusions: this model is important to understand the role of oxidative stress associated with increased metalloproteinase activity and vascular calcification.